2004
DOI: 10.1369/jhc.4a6291.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Antioxidant Enzymes in Developing Human Lung, Respiratory Distress Syndrome, and Bronchopulmonary Dysplasia

Abstract: We studied cell-specific protein expression of all the major antioxidant enzymes (AOEs) and related proteins, such as copper-zinc superoxide dismutase (CuZnSOD), manganese SOD (MnSOD), extracellular SOD (ECSOD), catalase, the heavy and light chains of γ-glutamylcysteine synthetase (γ-GCS-l and γ-GCS-h, also called glutamate cysteine ligase), the rate-limiting enzyme in glutathione synthesis, hemeoxygenase-1 (HO-1), and thioredoxin (Trx), in developing human lung, respiratory distress syndrome, and bronchopulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 54 publications
4
16
1
1
Order By: Relevance
“…Catalase was not detected in alveolar tissue even in the nonsmokers (data not shown). This is consistent with findings by KAARTEENAHO-WIIK and KINNULA [10], showing immunoreactivity of catalase in bronchiolar epithelium in human lungs. However, despite minimal change in bronchiolar catalase in smokers without COPD, a dramatic decrease in catalase staining in the cells of the terminal bronchioles was detected in smokers with COPD ( fig.…”
Section: Characteristics Of Human Subjectssupporting
confidence: 93%
See 1 more Smart Citation
“…Catalase was not detected in alveolar tissue even in the nonsmokers (data not shown). This is consistent with findings by KAARTEENAHO-WIIK and KINNULA [10], showing immunoreactivity of catalase in bronchiolar epithelium in human lungs. However, despite minimal change in bronchiolar catalase in smokers without COPD, a dramatic decrease in catalase staining in the cells of the terminal bronchioles was detected in smokers with COPD ( fig.…”
Section: Characteristics Of Human Subjectssupporting
confidence: 93%
“…Catalase is expressed during the later stages of lung development, and is constitutively expressed in airway and alveolar epithelial cells and in macrophages in adults [10]. To date, several studies have focused on catalase in pathological lung status [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, other potential regulatory mechanisms warrant investigation. Prior studies in the developing human lung (17-wk gestation) indicated that SOD2 expression is limited to the alveolar and bronchial epithelium as well as macrophages (13). However, our immunohistochemical data indicate that in the postnatal lamb lung, there is robust expression of SOD2 in both the endothelium and the smooth muscle layers of pulmonary arteries.…”
Section: Discussioncontrasting
confidence: 60%
“…eNOS is then said to be uncoupled. Under these conditions, superoxide is quickly converted into peroxynitrite if NO is also present locally, or into H 2 O 2 via superoxide dismutase (SOD) (22). H 2 O 2 is converted into H 2 O and O 2 by catalase and glutathione peroxidase (9).…”
mentioning
confidence: 99%